Diversity of Algae (Cholorophyceae) in Paddy Fields of Lalgutwa Area, Ranchi, Jharkhand - Amit Kumar and Radha Sahu (Journal of Applied Pharmaceutical Science)
The distribution of Chlorophyceae (Green algae) in relation to seasonal variation of paddy fields at Lalgutwa area, Ranchi has been under taken for the first time in this area. A regular seasonal collection has been made during several field trips in year 2010 to 2011. Total 24 chlorophycean taxa with wide range of thallus structure were collected belonging to various orders i.e., Chlorococcales, Ulotrichales, Cladophorales, Oedogoniales, Zygnematales etc. Moderate temperature, high light nutrient and water availability appears to be better conditions for algal growth in the rice field habitat. This study reveals that comparatively lesser number of Chlorophycean members is growing in summers in comparison to rainy and winter seasons.
Keywords: Temperature,Rice Field,Seasonal Variation